2003
DOI: 10.1161/01.cir.0000068312.21969.c8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ezetimibe Coadministered With Atorvastatin in 628 Patients With Primary Hypercholesterolemia

Abstract: Background-Despite the established efficacy of statins, many patients do not achieve recommended LDL cholesterol (LDL-C) goals. Contributing factors may be inadequate dosing, increased risk for adverse effects with high-dose monotherapy, and increased potential for intolerance and adverse effects with combinations of available agents. Methods and Results-In a double-blind study, 628 patients with baseline LDL-C 145 to 250 mg/dL and triglycerides Յ350 mg/dL were randomly assigned to receive 1 of the following f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
342
3
18

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 631 publications
(392 citation statements)
references
References 16 publications
(15 reference statements)
17
342
3
18
Order By: Relevance
“…For example, aspirin (Husain et al 1998) and the selective COX-2 inhibitor celecoxib (Widlansky et al 2003b) have both been shown to improve endothelium-dependent dilation. It is well established that cholesterol-lowering therapy also reduces systemic markers of inflammation, including CRP (Ballantyne et al 2003). On this basis, investigators have argued that the beneficial effects of statins on endothelial function in patients might also be attributable to pleiotropic anti-inflammatory effects (Bonetti et al 2003).…”
Section: Human Studies Of Systemic Inflammation and Endothelial Dysfumentioning
confidence: 99%
“…For example, aspirin (Husain et al 1998) and the selective COX-2 inhibitor celecoxib (Widlansky et al 2003b) have both been shown to improve endothelium-dependent dilation. It is well established that cholesterol-lowering therapy also reduces systemic markers of inflammation, including CRP (Ballantyne et al 2003). On this basis, investigators have argued that the beneficial effects of statins on endothelial function in patients might also be attributable to pleiotropic anti-inflammatory effects (Bonetti et al 2003).…”
Section: Human Studies Of Systemic Inflammation and Endothelial Dysfumentioning
confidence: 99%
“…40,46,47 Together, these data clearly demonstrate that the dual inhibition of both cholesterol synthesis and absorption is an attractive new strategy for the treatment of primary hypercholesterolemia.…”
Section: Efficacy Of Combination Therapy Using Ezetimibe With a Statinmentioning
confidence: 77%
“…In this study, 628 patients with baseline LDL-C 145-250 mg/dl were randomly assigned to receive one of the following for 12 weeks: ezetimibe 10 mg/day, atorvastatin (10, 20, 40, or Adding EZE to ATO 20 mg resulted in significantly greater reductions in LDL-C and significantly more pts achieving LDL-C \100 mg/dl Stein et al [48] 621 high-risk pts with LDL-C C130 mg/dl despite treatment with ATO 10 mg/day EZE 10 mg/day ? ATO 10 mg/day followed by response-based ATO dose titration up to 40 mg/day vs. monotherapy with ATO 20 mg/day with response-based ATO dose titration up to 80 mg/day Adding EZE to ATO 10 mg/day followed by ATO dose titration was more effective in reducing LDL-C and significantly increased the proportion of pts achieving LDL-C B100 mg/dl Ballantyne et al [49] 628 pts with primary hypercholesterolemia and baseline LDL-C 145-250 mg/dl [49]. Depending on atorvastatin dose, the ezetimibe-atorvastatin combination provided LDL-C reductions of 50-60%, triglyceride reductions of 30-40%, and HDL-C increases of 5-9%.…”
Section: Lipid-lowering Efficacy Of the Ezetimibe/ Atorvastatin Combimentioning
confidence: 99%
“…Despite some isolated reports of myopathy attributable to ezetimibe [73], the adverse event profile in several large trials was similar to that of placebo [74]. Studies assessing specifically the short-term safety of the atorvastatinezetimibe combination showed similar results, with no significant differences in the incidences of laboratory and clinical adverse events, including gastrointestinal, liver, or muscle effects [46][47][48][49][50]. Concerns that ezetimibe could increase the risk of cancer were raised by the SEAS trial.…”
Section: Safety Of the Ezetimibe-atorvastatin Combinationmentioning
confidence: 99%